MARKETING ONLINE TERHADAP MAHASISWA BARU UNTUK MEMILIH PERGURUAN TINGGI (STUDI KASUS UNIVERSITAS HARAPAN MEDAN) - Ronny Vickyh Ifanni Ar; Muhammad Fauzan Azhmy; Fajar Pasaribu (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This study aims to determine the effect of trust, convenience, quality of information and price on students' decisions to enter the University of Harapan Medan. This study uses an associative research type with a quantitative approach. The population in this study were students of Harapan University, Medan. Sources of data using primary data obtained by using a questionnaire. Data were analyzed using Multiple Linear Regression analysis technique. The results show that trust has a significant effect on college admission decisions. The magnitude of the contribution of trust in influencing college admission decisions is 0.663. This means that trust is very important because it can increase college admission decisions by 66.30%. Ease has a significant effect on college admission decisions. The magnitude of the contribution of convenience in influencing college admission decisions is 0.845. This means that convenience is very important because it can increase college admission decisions by 84.50%. The quality of information has a significant effect on college admission decisions. The magnitude of the contribution of information quality in influencing college admission decisions is 0.412. This means that the quality of information is very important because it can increase college admission decisions by 41.20%. Price has a significant effect on college admission decisions. The amount of price contribution in influencing college admission decisions is 0.517. This means that the price is very important because it can increase the decision to enter higher education by 51.70%.